Women in a man's world, crying : essays - Covington, Vicki (University of Alabama Press, 2002)
This thoughtful, engaging collection showcases the best nonfiction prose produced by one of the nation's most observant and incisive writers. This collection of warm, heartfelt essays from award-winning novelist Vicki Covington chronicles the multitude of "in between" moments in the writer's life. These are her stolen moments in between the writing of four novels-Gathering Home, Bird of Paradise, Night Ride Home, and The Last Hotel for Women; in between coauthoring the edgy memoir Cleaving: The Story of a Marriage with her husband Dennis Covington; in between raising two daughters; i